Automatic Response Category Combination in Multinomial Logistic Regression. Issue 3 (3rd July 2019) - Price, Bradley S.; Geyer, Charles J.; Rothman, Adam J.
Abstract: We propose a penalized likelihood method that simultaneously fits the multinomial logistic regression model and combines subsets of the response categories. The penalty is nondifferentiable when pairs of columns in the optimization variable are equal. This encourages pairwise equality of these columns in the estimator, which corresponds to response category combination. We use an alternating direction method of multipliers algorithm to compute the estimator and we discuss the algorithm's convergence. Prediction and model selection are also addressed. Supplemental materials for this article are available online.